Taxonomic and Ecogeographic Predictors of Resistance Against Phthorimaea operculella Zeller in Wild Potato Tubers - Horgan, F.G.; Portalanza, D.; Pelletier, Y.; Quiring, D.T. (Springer, 2023)
Taxonomic and ecogeographic information are potentially useful to select plants with beneficial traits for crop breeding. We tested the predictability of taxonomic and geoclimatic information in identifying wild potatoes with resistance in tubers to the potato tuber moth, Phthorimaea operculella Zeller. We tested the tubers of 47 wild potato species and the native potato Solanum tuberosum andigena for resistance to tuber moth larvae. Materials included 6585 genotypes representing 558 accessions. During screening, 28% of accessions had ≥ 60% undamaged tubers (moderate resistance) and of these, 10% were highly resistant to moth damage (i.e., ≥ 80% of tubers undamaged). Tubers of six potato species (S. commersonii, S. chiquidenum, S. albicans, S. acaule, S. demissum and S. boliviense) were significantly more resistant than tubers of S. tuberosum andigena, but resistant accessions also occurred among 22 other Solanum species. The frequency of resistant accessions was similar across phylogenetic clades, but resistance was more frequent in accessions with an endosperm balance number (EBN) of 1 or 4 and a ploidy level of 4 × or 6 × . There was no apparent relation between altitude of origin and tuber resistance. Ecogeographical information was weakly related to resistance in some potato species; minimum temperatures during the coldest months at collection sites were positively related to resistance in S. boliviense and S. medians. Mean high temperatures and summertime precipitation were positively related to resistance in S. microdontum and S. acaule, respectively; however, ecogeographic information was not generally useful in predicting tuber resistance for other species or across all species. We recommend improvements to the phenotyping of potato accessions for resistance to tuber moth, including the use of taxonomic predictors.